RASIONALITAS PILIHAN HIJRAH: Studi Fenomenologi Pilihan Hijrah Anggota Komunitas Kajian Humaira Surakarta - Inayah, Nur’aini (Jurnal Sosiologi Agama, 2020)
The phenomenon of hijrah began to widely spread in various places in Indonesia. The large number of public figures who identify themselves as doing hijrah makes the hijrah becomes the trends in society. This research aims to examine hijrah process and rationality of choosing hijrah among community members of Humaira. The theory used is the rationality theory of James C. Coleman who views that each individual performs an action based on their interests. The researcher employed a qualitative method with a phenomenology approach. Data sources in this research were (1) Primary Data (2) Secondary Data. The technique of informant collection used snowball technique. The researcher collected data using interview and observation techniques. The current research indicates two conclusions: First, the changes occurred to the members of Humaira community are different and the characteristics of hijrah experienced by each member are the same in which they experience one turning point in the form of life problems. Second, the hijrah process experienced by members of Humaira community is a rational choice. The hijrah movement that occurs is not only an emotional expression, but also accompanied by rationality that benefits the one doing hijrah.